FACTORS AFFECTING EMPLOYEE JOB SATISFACTION AT THE CLASS IB DISTRICT COURT OF LHOKSEUMAWE - Cut Amanda Fatma Zuhra; Ghina Najwa Ilmi; Azra Batrisia; M. Aria Maulana; Halimatus Sa’diyah; Maulizar Maulizar; Nursyidah Nursyidah (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to identify and analyze the factors that influence employee job satisfaction at the District Court of Lhokseumawe Class IB. The examined factors include internal factors such as work, promotion, and relationships with colleagues, as well as external factors such as salary and supervision. This research employs a quantitative approach using an associative method. The sample consists of 23 employees selected through a saturated sampling technique. The data were analyzed using multiple linear regression with the help of SPSS software. The results show that, partially, the variables of work, promotion, and supervision have a significant effect on job satisfaction. Meanwhile, the variables of coworker relationships and salary do not have a significant partial effect. Simultaneously, all independent variables have a significant effect on job satisfaction. These findings highlight the importance for management to focus on specific internal and external factors in order to enhance employee satisfaction and performance within the court environment.